A new 5-alkylresorcinol glucoside derivative from Cybianthus magnus. Issue 3 (1st February 2016) - Cabanillas, B.; Vásquez-Ocmín, P.; Zebiri, I.; Rengifo, E.; Sauvain, M.; Le, H.L.; Vaisberg, A.; Voutquenne-Nazabadioko, L.; Haddad, M.
Abstract : One new 5-alkylresorcinol glucoside (1 ) was isolated from leaves of Cybianthus magnus, along with 12 known compounds, isolated from four plants belonging to Myrsinaceae family (2, 3 isolated from C. magnus ;4 –7, 10 and11 isolated from Myrsine latifolia ;4, 8 and9 isolated from Myrsine sessiflora ;6, 7, 10, 12 and13 isolated from Myrsine congesta ). Their structures were determined on the basis of spectroscopic analysis and by comparison of their spectral data with those reported in the literature. So far, only nine 5-alkylresorcinol glucosides were isolated from leaves of Grevillea robusta . Since resorcinols are known to exhibit strong cytotoxic activity, compounds1 and2 were tested against cell lines 3T3, H460, DU145 and MCF-7 for cytotoxicity in vitro and compounds3 –13 were tested for their antileishmanial activity. Compound2 displayed a strong cytotoxic activity with IC50 values ranging between 22 and 100 μM for all tested cell lines. Compounds3 –13 were not active against Leishmania amazonensis amastigotes. Abstract : One new 5-alkylresorcinol glucoside (1 ) was isolated from leaves of Cybianthus magnus, along with 12 known compounds (2 –13 ), isolated from four plants belonging to Myrsinaceae family. Their structures were determined on the basis of spectroscopic analysis and by comparison of their spectral data with those reported in the literature. Among the tested molecules, only compound2 displayed a strong cytotoxic activity with IC50 values ranging between 22 and 100 μM for all cell lines tested.